(untitled) (Research, Society and Development, 2021)
Contemporary Western society is gendered, that is, structured based on the belief that there are two genders - male and female - that are mutually exclusive. This binary perception is supported by social devices that direct individuals to cisgenerity from the moment of birth, segregating divergent genders at the margins. Non-binary is an umbrella term that embraces gender identities that incorporate, to varying degrees, aspects of the male and female genders. Despite the rigor of the system, non-binary people even subvert language, highlighting the possibility of existing outside binarism. This proposal is justified by the need to expand the debate on non-binary identities and has the general objective of discussing the difficulties faced by non-binary people in cisnormative society. To this end, it adopts qualitative bibliographic research and discusses the binary system of gender, cisnormativity and its transgression. Then, talk about some gender expressions contained in the term non-binary umbrella. Finally, it exposes the main difficulties encountered by non-binary people.